2014
DOI: 10.1016/j.bpobgyn.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual aspects of vulvovaginal pain

Abstract: Vulvovaginal pain problems are major health concerns in women of childbearing age.Controlled studies have shown that vulvovaginal pain can adversely affect women and their partners' general psychological well-being, relationship adjustment and overall quality of life. These women have significantly lower levels of sexual desire, arousal, and satisfaction, as well as a lower intercourse frequency than normal controls. They also report more anxiety and depression, in addition to more distress about their body im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 51 publications
2
59
1
4
Order By: Relevance
“…STIs are a known direct cause of genital pain34 and although this may explain the association we found, it is also possible that previous experience of an STI leads some individuals to associate sex with disease, possibly engendering difficulties with arousal, and in turn, leading to painful sex 2. In contrast to previous research,7, 12, 31 we did not find an association of pain with frequency of intercourse. It has been suggested that some women simply endure their symptoms in order to continue having sex with their partner2, 35 and our inclusion of women with milder symptoms (compared with clinical samples) may have resulted in a higher proportion of women who continue to have sex despite their symptoms.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…STIs are a known direct cause of genital pain34 and although this may explain the association we found, it is also possible that previous experience of an STI leads some individuals to associate sex with disease, possibly engendering difficulties with arousal, and in turn, leading to painful sex 2. In contrast to previous research,7, 12, 31 we did not find an association of pain with frequency of intercourse. It has been suggested that some women simply endure their symptoms in order to continue having sex with their partner2, 35 and our inclusion of women with milder symptoms (compared with clinical samples) may have resulted in a higher proportion of women who continue to have sex despite their symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data confirm the strong link between pain and impaired sexual function found in the literature 2, 7, 12, 31. The relationship context of pain is beginning to receive more attention,7 but evidence of the link between sexual pain and relationship adjustment and satisfaction is equivocal 32.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations